Intergenerational mobility of economic well-being in Latin America - Guido Neidhöfer; Matías Ciaschi; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
We estimate, for the first time, long-run trends in intergenerational economic mobility for a multitude of countries in Latin America going beyond parent-child correlations in educational attainment. We use several indicators of well-being, such as the socio-economic situation of individuals, job stability, homeownership and assets. Unlike estimates based on education, which mostly show increasing social mobility trends, we find that opportunities to achieve a certain level of economic well-being and climb up the social ladder are rather unequally distributed and have not changed much over time in Latin America.
Keywords: D63; I24; J62; O15; 330; Inequality; Intergenerational Mobility; Equality of Opportunity; Well-being; Latin America